A New Reading of the Animal Apocalypse of 1 Enoch "All Nations Shall be Blessed" - Olson, Daniel C. 1955- (Boston Brill, 2013)
A New Reading of the Animal Apocalypse of 1 Enoch is the most comprehensive theological commentary on this important second-century BCE Jewish apocalypse to date, laying out the purpose and methodology of this Enochic allegory and using this as the basis for a new commentary on the whole text, presented here in a fresh translation. Against other interpretations that focus on Israel and its institutions, Daniel Olson argues that the promise of universal blessing in the Abrahamic covenant is presented in the Animal Apocalypse as the governing dynamic in a sacred history that begins and ends with humanity in general. The authentic Jacob/Israel will appear in the end times and be the catalyst of universal salvation
Machine generated contents note:1.Animal Apocalypse as Allegory --2.Unresolved Questions about the Animal Apocalypse --3.History and Theology in the Animal Apocalypse: Recent Scholarship --4.Present Study --5.Thesis --pt. ONEANIMAL APOCALYPSE AND THE OFFSPRING OF ABRAHAM --I.Looking at the Future: The Scope and the Focus of the Allegory --1.Is the Scope of the Allegory Particular or Universal? --2.Focus of the Allegory: Eschatological Transformation --a.nagar of 1 En 90:38 --b.Who Is the White Bull? --3.Enoch Tradition and the Abrahamic Covenant --4.Jacob and the Enochic Tradition --a.Jacob, Enoch, and the "Book of the Watchers" (1En 1-36) --b.Jacob, Enoch, and the "Astronomy Book" (1En 72-82) --c.Jacob, Enoch, and the "Admonitions of Enoch" (1En 91-105) --d.Jacob, Enoch, and the "Parables of Enoch" (1En 37-71) --e.Preliminary Conclusions, with a Caution --5.Jacob, Enoch, and the Animal Apocalypse --II.Looking at the Past: The Uses of History in the Allegory --1.Is There "History" between the Two Jacobs? --2.Qualifying for the Blessing --3."Open Eyes": Seeing the Glory of God --4.Enoch and Jacob: Seers of the Glory --5.Color and Location --a.Black versus White --b.Straying versus Staying-Returning --6.Three Dynamics --7.Conclusions --III.Looking at the Present: The Allegory in Its Own Historical Context --1.Why Support the Revolt? --2.Suiting the Allegory to Service as Propaganda --a.Sin of Fratricide --b.Strengths and Limitations of Leadership --c.Diplomatic Touch --3.Establishing a Two-Fold Authority --a.Authority of Enoch --b.Authority of Scripture and History --4.Predicting the End --5.Evidence of the Book of Jubilees --6.Conclusions --pt. TWOANIMAL APOCALYPSE (1 EN 85:2-90:42) TRANSLATION AND COMMENTARY --IV.Text of the Animal Apocalypse --V.Identifications of the Wild Animals in the Animal Apocalypse --1.Animals in 1En 89:10-11: Species --2.Animals in 1En 89:10-11: Ethnic/Political Identity --a."The Beasts of the Field" --b."The Birds of the Sky" --VI.Genesis through Kings (1 Enoch 85:2-89:58) Translation and Commentary --85:2-10: The First Generations of Humanity --86:1-87:1: The Fall of the Watchers and the Birth of the Giants --87:2-89:1: The Seven Archangels and the First Judgment --89:2-9: The Flood --89:10-14: Noah to Joseph --89:15-27: Moses and the Exodus --89:28-40: From the Exodus to the Settlement in the Land --89:41-50: From the Judges to Solomon --89:51-58: The Period of the Divided Kingdom --VII.Exile to the Eschaton (1 Enoch 89:59-90:42) Translation and Commentary --89:59-64: The Seventy Shepherds --89:65-72a: The First Period: The Babylonian Era --89:72b-90:1: The Second Period: The Persian Era --90:2-5: The Third Period: The Macedonian-Ptolemaic Era --90:6-12: The Fourth Period: The Seleucid Era --90:13-19: The Final War --90:20-27: The Last Judgment --90:28-36: The New Jerusalem --90:37-39: The New Humanity --90:40-42: Epilogue --pt. THREEANIMAL APOCALYPSE AND THE ONGOING CONVERSATION --VIII.Animal Apocalypse in Dialogue --1.Looking at the Past: The "Wisdom" Approach to History --2.Looking at the Present: The Jewish-Hellenistic Encounter and the Maccabean Revolt --3.Looking to the Future: The Eschatology of the Animal Apocalypse and the Apostle Paul --4.Conclusions --Appendix: Allusions to the Animal Apocalypse in the Epistle of Barnabas and the Coptic Apocalypse of Elijah --1.Epistle of Barnabas --2.Coptic Apocalypse of Elijah --3.Conclusions.
Includes bibliographical references and index
Keywords: Bible -- History of Biblical events; Ethiopic book of Enoch LXXXV-XC -- Criticism, interpretation, etc; Bible; Ethiopic book of Enoch LXXXV-XC; Jews -- History -- To 70 A.D; Apocalyptic Literature -- History and criticism; Animals -- Religious aspects; Animals -- Symbolic aspects; RELIGION ; Biblical Studies ; Bible Study Guides; Animals ; Religious aspects; Animals ; Symbolic aspects; Apocalyptic Literature; History of Biblical events; Jews; Criticism, interpretation, etc; History